Evaluating market risk from leveraged derivative exposures - Audrius Jukonis (European Central Bank (ECB), 2022)
Market participants use leveraged derivatives to gain access to equity market exposure through broker banks. Leverage and interconnectedness via overlapping portfolios of dealer banks can amplify adverse market movements, potentially causing sizeable losses. I propose a model, based on granular data, to simulate losses from a banks' trading book in case of an adverse market scenario. Following a move in asset prices, banks mark their positions and issue margin calls; some (leveraged) counterparties fail to pay their margins, forcing banks to liquidate their positions causing a pressure on asset prices due to market impact. The impact is amplified because of the leverage and when counterparties are exposed to multiple banks over the same underlying. I employ the model to assess current capital and margin rules in covering risks from broker's exposure to highly leveraged clients.
Keywords: C60; G23; G13; G17; 330; EMIR; market risk; leverage; Initial margin; Variation margin